(untitled) (Studia Archaeologica, 2025)
This study presents thirty newly discovered and documented deer stones from Khuvsgul Province in northern Mongolia, recorded during the 2022–2023 field seasons. The majority of these monuments-approximately 90 percent without animal depictions, a pattern that represents a distinctive regional characteristic of northern Mongolia. Several examples also bear engravings of bola weapons, a motif that is exceptionally rare within the broader deer stone tradition. Of particular significance is the Shiveet deer stone, which displays several previously undocumented features in deer stone art: a belt with multiple suspended objects, a diadem or headband rendered as a series of small circular hollows, and three circular depressions that appear to symbolize the three oblique lines typically carved on the front face. Together, these findings provide important new evidence for understanding the diversity, stylistic variation, and regional development of Deer Stone culture. Монголын умард нутгаас шинээр илрүүлсэн буган хөшөөд Хураангуй. Монгол улсын умард бүс Хөвсгөл аймгийн нутгаас 2022-2023 оны хооронд шинээр илрүүлэн, бүртгэн баримтжуулсан гучин буган хөшөөний талаар энэхүү судалгаанд авч үзлээ. Эдгээр буган хөшөөдийн ихэнх нь буюу 90 хувь нь амьтны дүрслэлгүй буган хөшөөд байгаа нь тухайн бүс нутгийн онцлогийг илэрхийлж байна. Зарим буган хөшөөнд уг соёлын хүрээнд маш цөөн тохиолдох гүйвэр зэвсэг дүрсэлснээс гадна Шивээтийн буган хөшөөнд урьд өмнө буган хөшөөнд огт тохиолдож байгаагүй агсарга унжлагатай бүс, олон цувраа хонхор цэгээр илэрхийлсэн титэм, нүүрэн талд дүрсэлдэг гурван ташуу зураасыг төлөөлүүлсэн гурван хонхор цэг зэргийг дүрсэлсэн нь уг соёлын судалгааг баяжуулсан маш чухал, шинэ баримтууд болж байна. Түлхүүр үг: Хүрлийн үе, буган хөшөө, Монголын умард нутаг, агсарга бүс, гүйвэр зэвсэг